2007
DOI: 10.1373/clinchem.2007.088302
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ScaI and Natriuretic Peptide (NP) Clearance Receptor Polymorphisms of the NP System on NP Concentration in Chronic Heart Failure

Abstract: Results: ScaI polymorphism had no effect on NP concentration in the NYHA I-II subgroup. Conversely, in severe HF, A1 carriers had higher ANP (P <0.05), BNP (P <0.01), and NT-proBNP (P <0.01) than A2A2 patients. After multivariate adjustment, A1 presence remained an independent predictor for increased NP. Regarding NPRC polymorphism in mild HF, higher ANP (P <0.05) and BNP (P <0.05) were observed in CC than A allele carriers. After multivariate adjustment, however, this association did not remain significant. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Two single nucleotide polymorphisms, rs5065 in an exon of NPPA (Vassalle et al, 2007) and rs1023252 in an intron of CLCN6 (Del Greco et al, 2011), showed association with NT-proBNP (N-terminal of the prohormone brain natriuretic peptide) levels in patients with cardiac dysfunction, indicating that these variants can affect the function of regulatory sequences. Genetic variants associated with hypertension (Flister et al, 2013) are positioned across a larger 300-kb region (from upstream of NPPB to downstream of Fig.…”
Section: Discussion the Nppa-nppb Cluster Is Confined To A Regulatorymentioning
confidence: 99%
“…Two single nucleotide polymorphisms, rs5065 in an exon of NPPA (Vassalle et al, 2007) and rs1023252 in an intron of CLCN6 (Del Greco et al, 2011), showed association with NT-proBNP (N-terminal of the prohormone brain natriuretic peptide) levels in patients with cardiac dysfunction, indicating that these variants can affect the function of regulatory sequences. Genetic variants associated with hypertension (Flister et al, 2013) are positioned across a larger 300-kb region (from upstream of NPPB to downstream of Fig.…”
Section: Discussion the Nppa-nppb Cluster Is Confined To A Regulatorymentioning
confidence: 99%
“…The C(-55) allele of the NPR3 gene was found also to be associated with family history of hypertension (54 ). However, our recent data did not show the C(-55) NPR3 polymorphism to be an independent determinant of NP concentration in HF (41 ).…”
Section: Biological Significance and Clinical Relevancementioning
confidence: 66%
“…Several polymorphisms in the NPR3 gene have been described, including the C(-55)A polymorphism in the promoter region of the NPR3 gene and a VNTR polymorphism consisting of a 6-nucleotide repeat 4 bp upstream from the major transcriptional initiation site in the 5Ј flanking region of the NPR3 gene (49,41,42,(52)(53)(54)(55)(56)(57).…”
Section: Natriuretic Peptide Receptor C/guanylate Cyclase C (Atrionatmentioning
confidence: 99%
“…[74][75][76] The C12orf30 is associated with type 1 diabetes, hypothyroidism, arthritis, systemic lupus erythematosus, other autoimmune disorders and prostate cancer. [77][78][79] The druggableness of the C12orf30 (enzyme) offers an attractive target for type 1 diabetes-associated disorders and complications.…”
Section: Discussionmentioning
confidence: 99%